Non-Tenure Track Faculty Satisfaction: A Self-Determination Model - Crick, Kent A. (2019)
Full-time non-tenure track faculty, commonly referred to as NTT faculty, are increasingly utilized in higher education and shoulder much of the teaching load within academic institutions. Self-determination theory (SDT) has shown promise as a conceptual frame for characterizing the relationship between environmental support factors and NTT faculty satisfaction. Full-time NTT faculty were sampled nationwide (N = 3,527) to investigate an SDT-based model positing basic psychological needs (i.e., volitional autonomy and relatedness) as mediators between six environmental support indices and NTT faculty satisfaction (i.e., teaching/service and global satisfaction). Structural equation model results showed volitional autonomy and relatedness fully mediated the relationships between the six environmental supports and both indices of faculty satisfaction. Results highlight the utility of basic psychological needs in understanding the relationships between the environment and NTT faculty satisfaction. Implications, future directions, and limitations are also presented